Cooperative problem-based learning enhances motivation in sustainability courses using the music model - Nugraha, Satriya; Towip, Towip; Widiastuti, Indah (Faculty of Engineering, Universitas Negeri Yogyakarta, 2025)
Motivation is crucial in education, driving the learning process. Cooperative Problem-Based Learning (CPBL), an extension of Problem-Based Learning (PBL), enhances critical thinking and student motivation, especially in mechanical engineering education. However, research on CPBL’s motivational impact is limited. The MUSIC Model—comprising Empowerment, Usefulness, Success, Interest, and Caring—provides a framework to boost motivation. This study examines the synergy between CPBL and the MUSIC Model in mechanical engineering education. A mixed-method approach with a Sequential Explanatory design was used, involving students from a public university in Surakarta, Indonesia, enrolled in a sustainability-related course. Quantitative data were collected through MUSIC-based questionnaires, and qualitative data were obtained from semi-structured interviews. Descriptive statistics (SPSS) and the Miles & Huberman method analyzed the data. Results show that 60-90% of students report very high motivation across all components. The study suggests CPBL fosters motivation and develops essential 21st-century skills, preparing students for future challenges.